Pengaruh Profitabilitas Dan Kebijakan Dividen Terhadap Nilai Perusahaan Manufaktur - Yusuf Faisal; Nopitasari; Widy Siti Widyarti (JURNAL AKUNTANSI DAN AUDIT TRI BHAKTI, 2023)
This study aims to determine whether the influence of Profitability on Firm Value and Dividend Policy on Firm Value in manufacturing companies in the general food and beverage consumption sector are listed on the Indonesia Stock Exchange for the 2017-2021 period. This study uses a quantitative approach. The population in this study are all manufacturing companies listed on the IDX. The sample determined by the purposive sampling method was 14 companies for 5 years (2017 - 2021). The analytical method used is multiple analysis. Data collection techniques use the reporting method through the official financial website www.finance.yahoo.com, www.idx.co.id, and the RTI Business application or www.rti.co.id. The data processing tool uses SPSS version 25. Hypothesis testing uses the t test and f test. Based on the results of the research, it shows that: 1) Profitability has a positive effect on firm value. 2) Dividend policy has a positive effect on firm value